61.10.12 problem 25

Internal problem ID [12199]
Book : Handbook of exact solutions for ordinary differential equations. By Polyanin and Zaitsev. Second edition
Section : Chapter 1, section 1.2. Riccati Equation. subsection 1.2.6-2. Equations with cosine.
Problem number : 25
Date solved : Tuesday, January 28, 2025 at 07:28:18 PM
CAS classification : [_Riccati]

\begin{align*} \left (a \cos \left (\lambda x \right )+b \right ) y^{\prime }&=y^{2}+c \cos \left (\mu x \right ) y-d^{2}+c d \cos \left (\mu x \right ) \end{align*}

Solution by Maple

Time used: 0.015 (sec). Leaf size: 268

dsolve((a*cos(lambda*x)+b)*diff(y(x),x)=y(x)^2+c*cos(mu*x)*y(x)-d^2+c*d*cos(mu*x),y(x), singsol=all)
 
\[ y = \frac {-d \left (\int \frac {{\mathrm e}^{\frac {c \left (\int \frac {\cos \left (\mu x \right )}{a \cos \left (\lambda x \right )+b}d x \right ) \sqrt {a^{2}-b^{2}}\, \lambda -4 d \,\operatorname {arctanh}\left (\frac {\left (a -b \right ) \tan \left (\frac {\lambda x}{2}\right )}{\sqrt {a^{2}-b^{2}}}\right )}{\sqrt {a^{2}-b^{2}}\, \lambda }}}{a \cos \left (\lambda x \right )+b}d x \right )+d c_{1} -{\mathrm e}^{\frac {c \left (\int \frac {\cos \left (\mu x \right )}{a \cos \left (\lambda x \right )+b}d x \right ) \sqrt {a^{2}-b^{2}}\, \lambda -4 d \,\operatorname {arctanh}\left (\frac {\left (a -b \right ) \tan \left (\frac {\lambda x}{2}\right )}{\sqrt {a^{2}-b^{2}}}\right )}{\sqrt {a^{2}-b^{2}}\, \lambda }}}{\int \frac {{\mathrm e}^{\frac {c \left (\int \frac {\cos \left (\mu x \right )}{a \cos \left (\lambda x \right )+b}d x \right ) \sqrt {a^{2}-b^{2}}\, \lambda -4 d \,\operatorname {arctanh}\left (\frac {\left (a -b \right ) \tan \left (\frac {\lambda x}{2}\right )}{\sqrt {a^{2}-b^{2}}}\right )}{\sqrt {a^{2}-b^{2}}\, \lambda }}}{a \cos \left (\lambda x \right )+b}d x -c_{1}} \]

Solution by Mathematica

Time used: 3.763 (sec). Leaf size: 289

DSolve[(a*Cos[\[Lambda]*x]+b)*D[y[x],x]==y[x]^2+c*Cos[\[Mu]*x]*y[x]-d^2+c*d*Cos[\[Mu]*x],y[x],x,IncludeSingularSolutions -> True]
 
\[ \text {Solve}\left [\int _1^x\frac {\exp \left (-\int _1^{K[2]}\frac {2 d-c \cos (\mu K[1])}{b+a \cos (\lambda K[1])}dK[1]\right ) (-d+c \cos (\mu K[2])+y(x))}{c \mu (b+a \cos (\lambda K[2])) (d+y(x))}dK[2]+\int _1^{y(x)}\left (-\int _1^x\left (\frac {\exp \left (-\int _1^{K[2]}\frac {2 d-c \cos (\mu K[1])}{b+a \cos (\lambda K[1])}dK[1]\right )}{c \mu (b+a \cos (\lambda K[2])) (d+K[3])}-\frac {\exp \left (-\int _1^{K[2]}\frac {2 d-c \cos (\mu K[1])}{b+a \cos (\lambda K[1])}dK[1]\right ) (-d+c \cos (\mu K[2])+K[3])}{c \mu (b+a \cos (\lambda K[2])) (d+K[3])^2}\right )dK[2]-\frac {\exp \left (-\int _1^x\frac {2 d-c \cos (\mu K[1])}{b+a \cos (\lambda K[1])}dK[1]\right )}{c \mu (d+K[3])^2}\right )dK[3]=c_1,y(x)\right ] \]